Facile hydrothermal method synthesis of coralline-like Li1.2Mn0.54Ni0.13Co0.13O2 hierarchical architectures as superior cathode materials for lithium-ion batteries. (March 2015) - Hou, Xianhua; Huang, Yanling; Ma, Shaomeng; Zou, Xiaoli; Hu, Shejun; Wu, Yuping
Graphical abstract: Highlights: A coralline-like Li1.20 Mn0.54 Ni0.13 Co0.13 O2 cathode was synthesized by hydrothermal method. Initial discharge capacity of 250.2 mAh g −1 for the cathode was obtained at 0.1 C. A high reversible specific capacity of 210.2 mAh g −1 after 100 cycles was acquired. The high capacity retention of 84.5% was obtained even after 200 cycles at 10 C. Abstract: A coralline-like lithium-rich layered cathode material with homogeneous composition of Li1.20 Mn0.54 Ni0.13 Co0.13 O2 has been successfully synthesized via a facile ethanolamine (EA)-mediated hydrothermal method route, with subsequent calcination at 850 °C. An initial specific discharge capacity of 250.2 mAh g −1 and a reversible specific capacity of 210.2 mAh g −1 after 100 cycles at a constant density of 25 mA g −1 (1 C = 250 mA g −1 ) are acquired. Even at 10 C, it still delivers a discharge capacity of approximately 100 mA h g −1, thereby indicating its excellent high power performance. The sample also shows enhanced cycling performance with 88.5%, 79.9% and 90.5% of capacity retention after 100 cycles at 0.5, 5 and 10 C rates, respectively. Besides, 84.5% of initial capacity is retained even after 200 cycles at 10 C. Consequently, the fascinating electrochemical performance may facilitate the coralline-like LMNCO composite to be a promising alternative cathode for LIBs with a high application potential.